Seismic performance of high-rise building under different excitation - Cheok, Jia Wei (2023)
The location of Malaysia is considered safe from seismic and not within the Pacific Ring of Fire but the Ranau’s earthquake in 2015 warned that Malaysia is no longer immune from seismic disasters. In the past, most of the buildings were not designed to resist seismic loadings and so created challenges and hazards for people in Malaysia. Most Malaysian perceive that they are free from the life-threatening seismic crisis but they are wrong. Structural performances and life safety of any civil engineering work in Malaysia were paid more concern and attention due to the significant hazard occur in this earthquake. Thus, buildings especially high-rise residential expected to be subject to substantial damages caused by earthquake tremors if the building’s structures are not assessed and eventually strengthened. This research aims to determine the vulnerability and behaviour of existing high-rise buildings under excitation. Furthermore, the cost implication of structural design to resist seismic can be evaluated. A 50-storey reinforced concrete high-rise building in Kuala Lumpur was used as an example in this study to demonstrate the seismic performance under different excitation by using Etabs finite element software. Different seismic load cases were applied in this simulation analysis to achieve the main objectives, which are STATIC EQ, RSA, THA-ACEH, THA-RAPIDKL, THA-ELCENTRO, THA-YERMO, and THA-ALDATENA. According to the findings of free vibration analysis, the natural period of the buildings was 5.942 sec. The result of the natural period for this research was close to the rule of thumb, which is the number of stories divided by 10 usually used to estimate the natural periods for the buildings. The results showed that buildings with irregular shapes tend to be torsional for the first three mode shapes due to asymmetry characteristics. Moreover, the behaviours and performances of the building’s structure are assessed in global and local components through compared the different output results. The results obtained have shown that different excitation influenced the behaviours and performance of the building with different load patterns. If seismic types are classified as local earthquakes and with higher peak ground acceleration, a higher total drift ratio will be produced as the building is required to resist higher lateral forces. For the distant seismic load cases, lesser damages caused to buildings due to seismic energy have reduced during travel for a distance. Besides, results showed that deflection increased with the height of the buildings indicated that higher buildings tend to be more sensitive toward lateral loads. The developed Etabs model showed that the existing building capable to resist STATIC EQ, RSA, THA-ACEH, and THA-RAPIDKL under performance level of Immediate Occupancy (IO), while categorized as Life Safety (LS) when subjected to THA-ELCENTRO, by referred to the FEMA 356 guideline. Meanwhile, the buildings failed to resist the seismic load when subject to THA-YERMO and THA-ALDATENA. It also found that the cost of implication increased as the peak ground acceleration of seismic increased, where the structural elements required more reinforcements to provide capacity for resisting lateral loads. The analysis outcome of the existing building can resist 5 seismic loads within the acceptable range with additional cost imposed on the building.